A three-dimensional progressive damage model for drop-weight impact and compression after impact. (February 2020) - Pham, Dinh Chi; Lua, Jim; Sun, Haotian; Zhang, Dianyun
In this paper, an enhanced three-dimensional continuum damage mechanics model is applied to predict the drop-weight impact response and compression after impact failure of a fiber-reinforced polymer composite specimen. The three-dimensional progressive damage model incorporates a three-dimensional maximum stress criterion to predict the intra-ply damage initiation, followed by a fracture-energy-based smeared crack model to capture the post-peak softening behavior. Driven by the dominant through-the-thickness failure under impact loading, a three-dimensional continuum damage model is implemented for the three-dimensional solid element via its explicit material model for Abaqus (VUMAT) to capture the effect of three-dimensional stress state and the interaction of matrix cracking and delamination. Abaqus' restart analysis capability is used to activate the compression after impact analysis using the final damage state from the dynamic impact analysis. Both the dynamic failure and the compression after impact are demonstrated via a suite of verification examples followed by the sensitivity analysis using distinct impact configurations. The predictive capability of the proposed three-dimensional damage model is first verified using a static open-hole tension test. Applications of the damage model are then demonstrated for simulations of the dynamic drop-weight tests and compression after impact tests. A comparative study on the developed method is performed using the results predicted from the open-source CompDam. A sensitivity study is also performed to demonstrate the impact energy-dependent failure mode. The proposed model has shown its advantages in performing a quick assessment of impact damage and its effects on the residual compressive strength.